Digital Giants Duel: How Go-Jek and Grab Are Transforming Indonesia's Economic Landscape - Aswar Rahmat; Wahdaniah, Wahdaniah; Bahasoan, Awal Nopriyanto; Muhammad Ridwan Hayadin; Fausiah, Fausiah (ProBisnis : Jurnal Manajemen, 2024)
This article examines the competition between two giant companies in Indonesia's application-based service industry, Go-Jek and Grab. This competition goes beyond just a business battle; It represents a conflict between the traditional and sharing economies that use digital technology to connect service providers with users directly. This theme is relevant in the context of the remarkable transformation of how business is conducted in the modern era. This article uses descriptive analysis methods to describe both companies' user growth, service variety, and customer satisfaction. Through case studies and content analysis, this article identifies critical themes such as technological innovation, marketing strategy, and regulatory challenges Go-Jek and Grab face. The results of the analysis show that these two companies facilitate people's daily lives and inspire innovation in the digital economy. This research provides deep insight into competition dynamics in the application-based service industry and its impact on Indonesian society and economy